Self-Employment Dynamics Across the Business Cycle: Migrants Versus Natives - Amelie F. Constant; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
Economically active people are either in gainful employment, are unemployed or self-employed. We are interested in the dynamics of the transitions between these states across the business cycle. It is generally perceived that employment or self-employment are absorbing states. However, innovations, structural changes and business cycles generate strong adjustment processes that lead to fluctuations between employment and self-employment, directly or through the unemployment state. Migrants are more likely to be sensitive to adjustment pressures than natives, since they have less stable jobs and choose more often self-employment to avoid periods of unemployment. These issues are investigated using a huge micro data set generated from 19 waves of the German Socioeconomic Panel. The findings suggest that the conditional probabilities of entry into selfemployment are more than twice as high from the status of unemployment as from the status of employment. Self-employment is also an important channel back to regular employment. Business cycle effects strongly impact the employment transition matrix, and migrants take a larger part in the adjustment process. They use self-employment as a mechanism to circumvent and escape unemployment and to integrate into the host country's labor market.
Keywords: E32; M13; J61; J23; 330; Self-employment; entrepreneurship; business cycle; migration; Markov chain analysis; Selbstständige; Erwerbsstatus; Konjunktur; Ethnische Gruppe; Panel; Deutschland